Performance of rice husk ash concrete at elevated temperatures - Kumar, P. Chandan; Rao, P. Malleswara; Balaji, K.V.G.D. (Journal of Structural Engineering, 2024)
In the present investigation, a feasibility study is made to utilize the Rice Husk Ash (RHA) as an admixture in concrete and to investigate the impact of elevated temperatures on compressive strength of concrete. The proportions of water, cement, fine aggregate and coarse aggregate for M 20 grade concrete is arrived as per IS: 10262 – 2007. 5%, 10%, 15%and 20% of cement is replaced with rice husk ash for the study to arrive at the optimum replacement and they are tested at room temperature, 100, 300, 500, 700 degrees centigrade temperatures. Use of rise husk ash in concrete not only reduces cost but also improves resistance against elevated temperatures and durability. The utilization of Rice Husk Ash in concrete is environmental friendly and reduces the carbon dioxide emission.